Impact of Artificial Intelligence on Cyber Security - Rashmi, BH (International Journal of Computer Sciences and Engineering, 2018)
As the technology is evolving day by day, new challenges are coming in a computing world. One such challenge is Cyber Security. Cyber Security is also termed as Computer security or Information Security. Cyber security experts are facing lot of problems with the outburst of technologies like IOT. In order to avoid these outbursts Cyber security experts should be aware of many security attacks and breaches and should be in a position to classify all the attacks and prevent the system from these types of attacks. But due to heavy traffic and many more security breaches, the areas under Cyber security threat can’t be handled by humans. It is quite difficult to create standard automation algorithms to prevent certain Cyber area threats. To implement these standard automation algorithms, an area of Intelligence called as Artificial Intelligence is adapted. Using these Intelligence techniques many security breaches and cyber-attacks can be avoided. This paper focuses on Artificial Intelligence applications and techniques for Cyber Security, in order to be responsive to many Cyber-attacks.